Pengelolaan Pariwisata yang Ramah Lingkungan Berbasis Masyarakat Lokal di Bukit Baranahu - Pelikwan; Meycel Pratama; Andika Sanjaya; Cyntia Lupita Sari (LP3M INSTITUT KH YAZID KARIMULLAH, 2026)
Sustainable tourism management has become a crucial issue in balancing economic benefits, environmental preservation, and social equity, particularly in local natural destinations. Bukit Baranahu in Central Kalimantan represents a growing rural tourism site that requires integrated and community-based governance to maintain its sustainability. Using a qualitative descriptive approach, data were collected through field observations, documentation, and limited stakeholder engagement involving local communities, tourism managers, and visitors. The findings indicate that initial efforts toward sustainability have been implemented, including community participation, local economic activities, and basic environmental conservation practices. However, significant challenges persist, particularly in waste management systems, infrastructure adequacy, environmental carrying capacity control, and long-term monitoring mechanisms. The analysis highlights that existing practices remain fragmented and require stronger institutional support and coordination. The study contributes by proposing a collaborative governance framework that integrates local government, community groups, tourism managers, and private stakeholders to enhance sustainability outcomes. Strengthening regulatory frameworks, improving environmental management systems, and fostering community capacity are identified as key strategies to ensure long-term viability of rural-based natural tourism destinations.